Pengembangan Media Scrapbook Berbasis Contextual Teaching and Learning (CTL) untuk Meningkatkan Literasi Saintifik Siswa Kelas IV SDN 1 Kawengan - Mardianti Dwiardhany; Decky Avriliand; Nuni Widiarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
. This research was motivated by the fact that the ability of scientific literacy of students in Natural and Social Sciences (IPAS) subject are not yet optimal, as well as the lack of variation in learning media that connects material with real life. This research aims to develop, test the feasibility, practicality, and effectiveness of scrapbook media based on Contextual Teaching and Learning (CTL) in improving scientific literacy of students at SDN 1 Kawengan. The type of research used is Research and Development (R & D) with the ADDIE model procedure (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research were fourth grade students of SDN 1 Kawengan. Data collection instruments include interview guidelines, expert validation sheets (material experts and media experts), response questionnaires (educators and students), and scientific literacy test instruments in the form of pre-test and post-test. The results of the research show that the CTL-based scrapbook media product developed is declared very feasible based on the validation results of experts. The practicality test results from the responses of educators and students also show very practical criteria. Furthermore, the effectiveness test through N-Gain test analysis shows a significant increase in scientific literacy scores between before and after using the media. Thus, it can be concluded that CTL-based scrapbook media is a media that is feasible, practical, and effective to use in improving the scientific literacy ability of students in IPAS learning at SDN 1 Kawengan.